Strategi Penguatan Budaya Religius dalam Membentuk Karakter Peserta Didik Di Madrasah - Amik Nadziroh (UIN Sunan Gunung Djati Bandung, 2019)
Quality Education must be equipped with indicators of religious values that are internalized in learners. Starting from that, it is very urgent for educational institutions, especially Elementary School Education or Madrasah Ibtidaiyah to interrelate religious values into students by implementing, incorporating religious culture through a program of habituation activities. Education is more dominated by the development of learners from the affective aspect, which is more likely to form the attitudes or characteristics of students. Effective religious culture is the values of trust, and actions as a result of mutual agreement give birth to the commitment of all personnel in a consistent and consistent manner, hence the culture schools have a big influence on the process of implementing character education. The success of strengthening religious culture in shaping the character of students can be applied by paying attention to approaches, methods, techniques, and evaluations.